2010
DOI: 10.1021/nn1003088
|View full text |Cite
|
Sign up to set email alerts
|

Flexible Germanium Nanowires: Ideal Strength, Room Temperature Plasticity, and Bendable Semiconductor Fabric

Abstract: The mechanical strengths of individual germanium (Ge) nanowires with 111 growth direction and diameters ranging from 23 to 97 nm were measured by bending each with a robotic nanomanipulator in a scanning electron microscope (SEM). The nanowires tolerate diameter-dependent flexural strains of up to 17% prior to fracture, which is more than 2 orders of magnitude higher than bulk Ge. The corresponding bending strength of 18 GPa is in agreement with the ideal strength of 14-20 GPa for a perfect Ge crystal. Nanowir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
106
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(107 citation statements)
references
References 30 publications
1
106
0
Order By: Relevance
“…However, these strains have recently been proven to be well within the realizable limit in nanowires. 8,9 Therefore, we predict that the phonon-limited mobility of Ge can be enormously enhanced by applying positive stress in the h111i direction, as shown in Fig. 1.…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…However, these strains have recently been proven to be well within the realizable limit in nanowires. 8,9 Therefore, we predict that the phonon-limited mobility of Ge can be enormously enhanced by applying positive stress in the h111i direction, as shown in Fig. 1.…”
Section: Resultsmentioning
confidence: 90%
“…The first type of strain has recently been achieved on thin films of Ge grown on In x Ga 1Àx As substrates, 7 where direct gap photoluminesence has been observed. Strains of the second type have been experimentally surpassed in nanowires, 8,9 where strains up to 17% have been achieved.…”
Section: Introductionmentioning
confidence: 99%
“…Following this report, large plasticity and the c-a transition have also been observed in other semiconductor NWs. Smith et al 75 observed that Ge NWs become amorphous at the point of maximum strain of 17%. Asthana et al 76 observed the c-a transition in the highly compressed region of the [0001] ZnO NWs after a number of loading and unloading cycles.…”
Section: Direct Atomic Mechanisms Of the Size Effect On The Unusual Pmentioning
confidence: 99%
“…These results provide a direct explanation for the ultra-large straining ability and the c-a transition mechanism for those semiconductor and ceramic nanostructures. 25,26,36,[75][76][77] …”
Section: Direct Atomic Mechanisms Of the Size Effect On The Unusual Pmentioning
confidence: 99%
“…The figure shows a snapshot of darkening after just 15 s at low magnification, corresponding to a lower dose than previous figures. Although the theoretical tensile strength of Ge is predicted to be 14-20 GPa [30,31] while undergoing an elastic deformation, experimental measurements range from 15 to 18 GPa [32,33] for Ge nanowires to just 40-95 MPa for bulk Ge [34]. This study indicates that tensile-strained Ge is Although the theoretical tensile strength of Ge is predicted to be 14-20 GPa [30,31] while undergoing an elastic deformation, experimental measurements range from 15 to 18 GPa [32,33] for Ge nanowires to just 40-95 MPa for bulk Ge [34].…”
Section: Discussionmentioning
confidence: 99%